Herpes Simplex Virus Type 1 and 2 Glycoprotein C Prevents Complement-Mediated Neutralization Induced by Natural Immunoglobulin M Antibody - Hook, Lauren M. (American Society for Microbiology, 2006)
Glycoprotein C (gC) of herpes simplex virus type 1 (HSV-1) and type 2 (HSV-2) binds complement component C3b and protects virus from complement-mediated neutralization. Differences in complement interacting domains exist between gC of HSV-1 (gC1) and HSV-2 (gC2), since the amino terminus of gC1 blocks complement C5 from binding to C3b, while gC2 fails to interfere with this activity. We previously reported that neutralization of HSV-1 gC-null virus by HSV antibody-negative human serum requires activation of C5 but not of downstream components of the classical complement pathway. In this report, we evaluated whether activation of C5 is sufficient to neutralize HSV-2 gC-null virus, or whether formation of the membrane attack complex by C6 to C9 is required for neutralization. We found that activation of the classical complement pathway up to C5 was sufficient to neutralize HSV-2 gC-null virus by HSV antibody-negative human serum. We evaluated the mechanisms by which complement activation occurred in seronegative human serum. Interestingly, natural immunoglobulin M antibodies bound to virus, which triggered activation of C1q and the classical complement pathway. HSV antibody-negative sera obtained from four individuals differed over an approximately 10-fold range in their potency for complement-mediated virus neutralization. These findings indicate that humans differ in the ability of their innate immune systems to neutralize HSV-1 or HSV-2 gC-null virus and that a critical function of gC1 and gC2 is to prevent C5 activation.